Second-order Fermi acceleration as the origin of the Fermi bubbles - Mertsch, P; Sarkar, S (Elsevier, 2012)
Gamma-ray data from Fermi-LAT show a bi-lobular structure extending up to 50° above and below the Galactic centre, coincident with a possibly related structure in the ROSAT X-ray map which presumably originated in some energy release close to the centre a few million years ago. It has been argued that the gamma-rays arise due to inverse Compton scattering of relativistic electrons accelerated at plasma shocks present in the bubbles. We explore the alternative possibility that the relativistic electrons undergo stochastic second-order Fermi acceleration in the entire volume of the bubbles by plasma wave turbulence. This turbulence is generated behind the outer shock and propagates into the bubble volume, leading to a non-trivial spatial variation of the electron spectral index. Rather than a constant volume emissivity as predicted in other models we find an almost constant surface brightness in gamma-rays and also reproduce the observed sharp edges of the bubbles. We comment on possible cross-checks in other channels.